Stephen Covey / Robert Heller ; alih bahasa Irzam Hardiansyah ; editor Sarah Rosinta Hutauruk, Theresia Vini s, Yati Sumiharti - Heller, Robert; Hardiansyah, Irzam; Hutauruk, Sarah Rosinta; Vini s, Theresia; Sumiharti, Yati (Esensi, 2008)
111 hlm ilus 21 cm